468 Prevalence of child abuse among children aged 11 to 17 years old in community settings of Karachi, Pakistan. (1st September 2016) - Lakhdir, Maryam; Kadir, Masood; Azam, Iqbal; Parpio, Yasmin; Khan, Uzma; Razzak, Junaid
Abstract : Background: Harsh disciplinary practices are considered common in developing countries. However, scientific evidence lacks to support this. Primary aim of this study was to determine the prevalence of different forms (physical, emotional maltreatment and neglect) of child abuse in Karachi, Pakistan. Methods: A cross sectional survey of 800 dyads (children ranging from 11–17 years old and their parent) were selected from 32 clusters of Karachi, using multistage cluster sampling between December 2014 to March 2015. A structured questionnaire adopted from International society of child abuse and neglect (International child abuse screening tool for parent and child). Prevalence of child maltreatment was estimated by mean child abuse score. Results: Mean score were 51.7 + 11.9 (child), 77.9 + 20.2 (mother) and 63.6 + 17.3 (father). Both parent and child responses revealed similar prevalence (43%) of child maltreatment. The mother's responses showed a prevalence of physical (42%), emotional (50%) maltreatment and neglect (5.4%) whereas, father's responses showed a prevalence of physical (39%), emotional (46%) maltreatment and neglect (9.7%). The child's experiences showed a prevalence of physical (49%), emotional (50%) maltreatment and neglect (57%). A substantial proportion of participants were exposed to at-least one form of maltreatment on mother (58%), father (54%) and child (74%) responses, of which all three maltreatment forms experienced by children were 4%, 9% and 31% on mother, father and child responses respectively. Conclusions: This study reflects hidden extent of child maltreatment and poly-victimisation in Karachi. Our findings provide evidence to raise public awareness about malpractices and highlight the need to develop positive parenting program.